Análisis socioeconómico de los créditos otorgados por el Banco Nacional de Fomento sucursal La Maná a los productores de cacao periodo 2011-2013 - Giler Quiróz, Silvana Mariuxy (2014)
The productive sectors of the country are in constant activity, their dynamics keeps the population economy stable, which is reflected in the gradual development of the cities, however, this reality is not the same in the rural sector, where despite the existence of an ongoing process in agricultural production, the results do not completely satisfy the needs of families that depend on this activity. In this regard, the Development National Bank, as a public financial institution, has among its objectives to look after the needs of agriculture to increase production and help with marketing to overcome economic and political expectations, to improve the living conditions of farmers....